THE PREZENTATION OF SELF IN EVERYDAY LIFE - IMPRESSION MANAGEMENT STRATEGIES WITHIN EMPLOYMENT INTERVIEW - USM ADMIN (Moldova State University, 2018)
The presentation of self in the most favorable light is a necessary skill in social life, as regardless the field in which we operate, the impression a person can make on others is an important and sometimes decisive aspect of interpersonal relationships or/and occupational success. The study describes the strategies used by job vacancies candidates within employment interviews and the way this influences the hiring decision, as the job interview is most often the gateway to any company, there is a strong interest manifested by social science researchers. Keywords: impression management, self-image, public image, social interactions, presentation, impression management strategies, self presentation.